2015
DOI: 10.1002/jbm.a.35454
|View full text |Cite
|
Sign up to set email alerts
|

Heparinized nanohydroxyapatite/collagen granules for controlled release of vancomycin

Abstract: The purpose of this study was to develop a bone substitute material capable of preventing or treating osteomyelitis through a sustainable release of vancomycin and simultaneously inducing bone regeneration. Porous heparinized nanohydroxyapatite (nanoHA)/collagen granules were characterized using scanning electron microscopy, microcomputed tomography and attenuated total reflectance Fourier transform infrared spectroscopy. After vancomycin adsorption onto the granules, its releasing profile was studied by UV mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Singh et al [ 54 ] demonstrated that active agents were released much slower from underloaded matrices compared to those loaded to capacity or overloaded. However, vancomycin has not been observed to bind to collagen [ 55 ], meaning that the loading capacities for vancomycin were well exceeded by the amounts used in our study, and no sustained release was to be expected. In all of our experiments only 80–90% of the vancomycin could be recovered after 24 h. This could not be attributed to vancomycin interaction with the used plasticware (data not shown).…”
Section: Discussionmentioning
confidence: 75%
“…Singh et al [ 54 ] demonstrated that active agents were released much slower from underloaded matrices compared to those loaded to capacity or overloaded. However, vancomycin has not been observed to bind to collagen [ 55 ], meaning that the loading capacities for vancomycin were well exceeded by the amounts used in our study, and no sustained release was to be expected. In all of our experiments only 80–90% of the vancomycin could be recovered after 24 h. This could not be attributed to vancomycin interaction with the used plasticware (data not shown).…”
Section: Discussionmentioning
confidence: 75%
“…The electrostatic energy of HAp was reported to play a role in the interaction between drugs and the HAp surface . Given that the surface of c plane of HAp is negatively charged, cationic VCM can adsorb onto HAp because the amino groups of the VCM are protonated . As TEIC resembles the structure as VCM as they both are glycopeptide antibiotics, charge‐based interactions may likewise account for TEIC high adsorbability to HAp .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, nanosized HAp demonstrates great potential as delivery vehicle for molecules such as proteins, drugs and DNA [11,13]. Besides its established biocompatibility [13,14], its high specific surface area and high surface reactivity promote an easy binding of great amount of molecules through simple adsorption [15][16][17]. In addition, its small size precludes immune system activation [13].…”
Section: Introductionmentioning
confidence: 99%